2004
DOI: 10.1110/ps.03407704
|View full text |Cite
|
Sign up to set email alerts
|

Conformational mapping of the N‐terminal peptide of HIV‐1 gp41 in lipid detergent and aqueous environments using 13C‐enhanced Fourier transform infrared spectroscopy

Abstract: The N-terminal domain of HIV-1 glycoprotein 41,000 (gp41) participates in viral fusion processes. Here, we use physical and computational methodologies to examine the secondary structure of a peptide based on the N terminus (FP; residues 1-23) in aqueous and detergent environments.12 C-Fourier transform infrared (FTIR) spectroscopy indicated greater ␣-helix for FP in lipid-detergent sodium dodecyl sulfate (SDS) and aqueous phosphate-buffered saline (PBS) than in only PBS. 12C-FTIR spectra also showed disordere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 78 publications
4
74
0
1
Order By: Relevance
“…The crystal structure of this peptide bound to 4E10 verifies a helical conformation, in which the hydrophobic residues are located on one face of the helix (9). The fusogenic peptide, however, could adopt an ␣-helical shape or a ␤-sheet conformation depending on the peptide concentration and environmental factors such as type of lipids or the presence of cations (21)(22)(23)(24)(25)(26). The PTMR as well as the N-terminal regions of gp120 and gp41 contain several hydrophobic residues.…”
Section: Lwvtvyygvpvwkmentioning
confidence: 92%
“…The crystal structure of this peptide bound to 4E10 verifies a helical conformation, in which the hydrophobic residues are located on one face of the helix (9). The fusogenic peptide, however, could adopt an ␣-helical shape or a ␤-sheet conformation depending on the peptide concentration and environmental factors such as type of lipids or the presence of cations (21)(22)(23)(24)(25)(26). The PTMR as well as the N-terminal regions of gp120 and gp41 contain several hydrophobic residues.…”
Section: Lwvtvyygvpvwkmentioning
confidence: 92%
“…Models for the helical structure have been developed based on nuclear magnetic resonance (NMR), electron spin resonance (ESR), infrared (IR), and circular dichroism (CD) data, as well as computer simulations (33)(34)(35)(36)(37)(38)(39). A β hairpin model for non-helical structure has been proposed based on IR and surface activity measurements in membranes (40).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Other investigators have developed structural models for the helical form of the peptides based principally on liquid-state NMR, ESR, and IR data (33,38,39,73,74). IR and solid-state NMR studies of the β strand form of HFP and its oligomeric constructs have shown parallel strand arrangement, anti-parallel strand arrangement and a mixture of parallel and antiparallel arrangements (26,43,44).…”
Section: Conformational Plasticitymentioning
confidence: 99%
“…Also, we have previously studied the HIV-1 fusion peptide FP-1 in an SDS micelle, 22,31 and the antimicrobial ovispirin and its derivatives in both SDS and DPC. 32,33 We detail here the simulation method used, present the results, and discuss the hypotheses we can generate about the activity and toxicity of protegrin-1.…”
Section: Introductionmentioning
confidence: 99%